Evaluation of corn fermented protein (CFP) in pet food applications - Kilburn-Kappeler, Logan Rylee (Kansas State University, 2023)
Co-products from the ethanol industry, such as distillers dried grains with solubles (DDGS) and corn fermented protein (CFP), can provide alternative protein sources for pet food. Corn fermented protein is produced using post-fermentation technology to split the protein and yeast from fiber prior to drying. This results in a higher protein ingredient compared to DDGS, increasing its appeal for pet food while still providing a sustainable and cost-effective ingredient. Corn fermented protein also contains a substantial yeast component which may provide health benefits. Therefore, the objectives of this work were to determine: 1) the optimal inclusion level of CFP for use in pet food and 2) the contribution from the yeast component of CFP on overall nutrition and animal health. To achieve these objectives, the effects of CFP on extrusion processing, kibble quality, palatability, nutrient digestibility, stool quality, and the fecal microbiome were assessed when fed to both dogs and cats. The first experiment evaluated diets with increasing levels of CFP in exchange for soybean meal at 0, 5, 10, and 15% (0C, 5C, 10C, 15C). The second experiment compared a diet containing 17.5% CFP to diets containing either 15% soybean meal (CON), 3.5% brewer’s dried yeast (BDY), or 2.5% brewer’s dried yeast plus 17.5% DDGS (BDY+DDGS). Titanium dioxide was added to all diets as a marker to estimate digestibility. Diets were fed to 12 dogs or 11 cats in a 4x4 replicated Latin square design. Animals were fed each dietary treatment for 9-d adaptation followed by 5-d total fecal collection. Fresh fecal samples from the second experiment were analyzed by 16S Metagenomic Sequencing. All data were analyzed using a mixed model in SAS (version 9.4, SAS Institute, Inc., Cary, NC) with treatment as a fixed effect and animal and period as random effects. For the first experiment, dry bulk density of kibble decreased while kibble toughness increased with CFP inclusion (P < 0.05). Dry fecal output was greater for dogs and cats fed increased levels of CFP (P < 0.05). Overall, nutrient digestibility decreased with increased levels of CFP. For palatability assessment, cats preferred 5C over 0C whereas dogs preferred 0C over 10C and 15C (P < 0.05). For the second experiment, preconditioner discharge temperature was greater for CON and BDY compared to BDY+DDGS and CFP (P < 0.05). Extruder screw speed, die temperature, kibble toughness, and kibble hardness were greatest for CFP (P < 0.05). The bulk density of BDY+DDGS at 392 g/L was greater than BDY and CFP at an average of 342 g/L (P < 0.05). The sectional expansion index of kibble for CFP was greater than BDY+DDGS and smaller than CON (P < 0.05) but similar to BDY. Fecal output was greatest for cats and dogs fed BDY+DDGS (P < 0.05). Overall, nutrient digestibility was lowest for BDY+DDGS when fed to both dogs and cats. There were no differences in total short chain or branched chain fatty acid concentrations in fresh fecal samples of dogs or cats fed dietary treatments (P > 0.05). For palatability assessment, dogs and cats had no preference when CON was compared to BDY or BDY+DDGS (P > 0.05). However, they appeared to prefer CON over CFP (P < 0.05). For the microbiome analysis, alpha-diversity indices (Observed, Chao1, Shannon, Simpson) and beta-diversity metric (principal coordinate analysis) were similar among all treatments in fecal samples from dogs and cats. There were no quantifiable shifts in predominant phyla among treatments in dogs (P > 0.05). However, in cats, the relative abundance of Firmicutes and Actinobacteria was lower for BDY+DDGS compared to CFP and BDY, respectively (P < 0.05). There were multiple significant differences in the relative abundance of genera among dietary treatments in both dogs and cats. Overall, the variation in dietary fiber content among treatments likely contributed to the difference in results. In order to maintain stool quality, nutrient digestibility, and palatability when fed to dogs or cats, a 10% inclusion of CFP would be recommended if exchanged for soybean meal in pet food. Further research is warranted to determine the ideal inclusion level of CFP in pet food to promote animal health.
Keywords: Cats; Corn fermented protein; Dogs; Nutrient digestibility; Extrusion; Fecal microbiome